Failure to Pay Claims of Insurance Policyholders Seen from the Principle of Absolute Responsibility - Yakob, Mita Rofiana (Estudiante Law Journal, 2024)
This study aims to analyze aspects of the mechanism for implementing the principle of absolute responsibility of life insurance companies pt. Life insurance for default on the policyholder's claim. The type of research used by researchers in compiling this research is a type of normative legal research. The results showed that the form of legal responsibility of PT. Life Insurance against policyholders when the company defaults on the incapacity of PT. AsuransiJiwasraya in fulfilling its obligations can be said to be an act of default and includes violations of Law Number 40 of 2014 Article 31 paragraph (3) which explains that insurance companies are required to handle claims and complaints through a fast, simple, accessible, and fair process and also violate Article 31 paragraph (4) which states that insurance companies are prohibited from taking actions that can slow down the settlement or payment of claims,  or not doing the action that should have been done. Due to the absence of an article regarding legal liability in the Super Jiwasraya Plan insurance policy, violations of Article 31 paragraphs (3) and (4) should be the basis for sanctions to be imposed on insurance companies contained in Article 71 in the form of written warnings, restrictions on business activities for part or all of business activities, prohibitions on marketing insurance products or sharia insurance products for certain business lines,  revocation of business licenses, administrative fines